2015
DOI: 10.1111/his.12560
|View full text |Cite
|
Sign up to set email alerts
|

Cell block samples from malignant pleural effusion might be valid alternative samples for anaplastic lymphoma kinase detection in patients with advanced non‐small‐cell lung cancer

Abstract: Malignant pleural effusion cell block samples had a diagnostic performance for ALK detection in advanced NSCLC that was comparable to that of tumour tissue samples. MPE cell block samples might be valid alternative samples for ALK detection when tissue is not available. Ventana IHC could be the most suitable method for ALK detection in MPE cell block samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 18 publications
(39 reference statements)
1
50
0
Order By: Relevance
“…FISH using fresh pleural fluid samples should be considered as an additional informative assay for pleural effusions suspicious of being malignant [40, 41]. Furthermore, cell block preparations are commonly used for diagnostic pathology and gene analysis by FISH and IHC [42, 43]. A few reports reported that compared with tumor tissue, pleural effusion cell block had 81.8% sensitivity and 80% specificity for detection of EGFR mutation [44] and 62.5% to 100% sensitivity and 100% specificity for ALK detection [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FISH using fresh pleural fluid samples should be considered as an additional informative assay for pleural effusions suspicious of being malignant [40, 41]. Furthermore, cell block preparations are commonly used for diagnostic pathology and gene analysis by FISH and IHC [42, 43]. A few reports reported that compared with tumor tissue, pleural effusion cell block had 81.8% sensitivity and 80% specificity for detection of EGFR mutation [44] and 62.5% to 100% sensitivity and 100% specificity for ALK detection [43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cell block preparations are commonly used for diagnostic pathology and gene analysis by FISH and IHC [42, 43]. A few reports reported that compared with tumor tissue, pleural effusion cell block had 81.8% sensitivity and 80% specificity for detection of EGFR mutation [44] and 62.5% to 100% sensitivity and 100% specificity for ALK detection [43]. For successful detection of the targeted gene, sufficient amount of malignant cells are needed; however, in some cases, like our patient (Fig 1), the amount of malignant cells in cell block samples are few.…”
Section: Discussionmentioning
confidence: 99%
“…Activated ALK could inhibit apoptosis and promote the proliferation through activation of down-stream PI3K/Akt and MAPK signalling pathways [17]. Accumulating evidence suggests that ALK was increased in a variety of tumors, including lung cancer [18], neuroblastoma [19], pancreatic cancer [20] and glioblastoma [21]. Martinengo et al found that under hypoxic conditions ALK directly regulated the abundance of hypoxia-inducible factors (HIFs) in both anaplastic large cell lymphoma and non-small cell lung carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding ALK genetic analysis, although fluorescent in-situ hybridization is considered to be the gold standard technique, two recent head-to-head comparison studies showed that RT-PCR [18] and Ventana immunohistochemistry [19] are better candidate methodologies when applied to blocks of pleural effusion cells. ALK rearrangement detection rates were 4.5% (3/66) and 15.4% (8/52), respectively.…”
Section: Key Pointsmentioning
confidence: 99%